2022
DOI: 10.1093/ntr/ntac018
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Prenatal Nicotine, THC, or Co-Exposure on Cognitive Behaviors in Adolescent Male and Female Rats

Abstract: Introduction Although there has been a decrease in the prevalence of tobacco smoking, exposure to nicotine during pregnancy remains a substantial problem worldwide. Further, given the recent escalation in e-cigarette use and legalization of cannabis, it has become essential to understand the effects of nicotine and cannabinoid co-exposure during early developmental stages. Methods We systematically examined the effects of nic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 95 publications
2
7
0
Order By: Relevance
“…Our results indicate that prenatally THC-exposed rats display an impairment in memory formation when they are requested to remember the unlike rewarded can, independently from its position, day by day. These results are consistent with data from the adolescent offspring of mothers exposed to higher doses of THC that exhibited deficits in visual discrimination in the novel object recognition test (NORT) [ 76 ] and alterations in main hippocampal oscillations [ 63 ]. Indeed, if the perirhinal and entorhinal cortices take part in object recognition memory, and particularly in object discrimination when complex stimuli must be processed [ 77 , 78 , 79 ], the hippocampus operates as the hub where direct and indirect projections carrying spatial/object memory information are integrated and encoded [ 80 , 81 , 82 ].…”
Section: Discussionsupporting
confidence: 89%
“…Our results indicate that prenatally THC-exposed rats display an impairment in memory formation when they are requested to remember the unlike rewarded can, independently from its position, day by day. These results are consistent with data from the adolescent offspring of mothers exposed to higher doses of THC that exhibited deficits in visual discrimination in the novel object recognition test (NORT) [ 76 ] and alterations in main hippocampal oscillations [ 63 ]. Indeed, if the perirhinal and entorhinal cortices take part in object recognition memory, and particularly in object discrimination when complex stimuli must be processed [ 77 , 78 , 79 ], the hippocampus operates as the hub where direct and indirect projections carrying spatial/object memory information are integrated and encoded [ 80 , 81 , 82 ].…”
Section: Discussionsupporting
confidence: 89%
“…Similarly, another study found that PNE males displayed anxiety-like behaviour in the EPM and marble burying test across more exposure periods than did females; additionally, only males showed anxiety-like behaviour in the light/dark box test and Novelty Suppressed Feeding Test (Alkam et al, 2013a). This last finding has also been seen using vapour exposure, with PNE males exhibiting more anxiety-related behaviours than females (Lallai et al, 2022). While males appear to be more vulnerable to anxiety-like behaviours after PNE in preclinical studies (see Table 2), the paucity of research and inconsistent methods make conclusions on sex differences in anxiety-related behaviour after PNE difficult.…”
Section: Zhang Et Al 2019mentioning
confidence: 68%
“…Of these, 432 were excluded for the following reasons: commentaries or reviews ( n = 71); neurodevelopment, cognitive, or behavioral outcomes ( n = 72); other unrelated health outcomes ( n = 86); studies of hemp oil, synthetic or endogenous cannabinoids, or the endocannabinoid system ( n = 36); polysubstance use or drugs other than cannabis ( n = 24); characteristics or reasons for cannabis use ( n = 43); prevalence studies ( n = 18); biomarker studies ( n = 16); cessation or prevention studies ( n = 9); health policy analyses ( n = 3); effects of pre-conception cannabis use ( n = 3); abstracts or reports presenting insufficient data ( n = 2); and papers focused entirely on unrelated exposures and outcomes ( n = 50). Thus, 47 epidemiologic studies [ 3 , 4 , 14 18 , 19 ••, 20 28 , 29 •, 30 33 , 34 ••, 35 58 ] and 12 animal models [ 59 , 60 ••, 61 , 62 , 63 ••, 64 , 65 ••, 66 •, 67 70 ] presenting original data met the inclusion criteria for this review.…”
Section: Resultsmentioning
confidence: 99%